Classical Islamic Leadership and The Consolidation of Power in The Umayyad Dynasty: A Study of The Reign of Al-Walid ibn Abd al-Malik (86–96 AH) - Risdayanti (UIN Sunan Gunung Djati Bandung, 2026)
This article examines the leadership of Al-Walid bin Abdul Malik in consolidating the power of the Umayyad Dynasty through political stability, territorial expansion, infrastructure development, as well as social and administrative integration. The study is based on the limited analytical research specifically addressing governance strategies during Al-Walid’s reign. The findings reveal that Al-Walid’s leadership successfully strengthened political legitimacy through systematic expansion, bureaucratic consolidation, and large-scale infrastructure development, both religious and social. In addition, policies of administrative standardization and Arabization played a significant role in reinforcing socio-political integration across diverse regions. These strategies not only created political stability but also fostered the advancement of Islamic civilization. Thus, effective leadership in the context of classical Islam was determined by the synergy between political authority, institutional development, and social integration. This study contributes to the development of Islamic leadership theory and provides practical implications for contemporary governance.